WORK SAFETY IN AGRICULTURAL PACKING HOUSES - ABRAHÃO, ROBERTO F.; TERESO, MAURO J. A.; MARTINS, MARCO A. (Revista Brasileira de Engenharia de Biossistemas, 2009)
This research's main objective was the identification of the risk factors of labour (work-related) accidentsin packing houses. Open and semi-structured interviews, photografic and filmed registers, directobservations and systematic observations of tasks had been carried through in six Campinas region'sUB. The EWA application allowed the understanding of the workers' difficulties, relative to aspects ofworkplace safety, analysed on the grounds of Labour Laws (NR) and Brazilian Standard 5413 (NBR).The risks were classified in Physical, Chemical, Biological, Ergonomic and of Accident. For each identifiedrisk, were presented the possible consequences and suggestions. As a product of this work, it was builta detailed checklist, containing many objective questions, relative to the aspects of workplace safety intomato processing unities.